A person's face complex image processing in the visible and infrared ranges for current psycho-emotional and functional state monitoring systems - Kolobashkina, Lyubov V.; Filippova, Aleksandra T. (2018 IEEE Conference of Russian Young Researchers in Electrical and Electronic Engineering (EIConRus), 2018)
Minimization of the so-called human factor influence on the reliability of the hazardous objects functioning is an urgent scientific, methodical and practical task. Continuous monitoring of the current psycho-emotional and functional state of the management operator is the main tool for managing the human factor. The paper suggests an approach to image integrated processing of the operator's face in the visible and infrared ranges. The essence of the approach is to take advantage of either one of the other image processing options to effectively solve the problems of searching for a person in the frame, highlighting the areas of the eyes, pupils, and also remote measurement of the main bio-parameters. The approach allows to significantly improve the reliability and efficiency of the above problems solution.